Gender Sensitive Agricultural Technology Development In The Indonesian Timor Semi-arid Farming System - Hesti R. Wijaya (Program Pascasarjana Universitas Brawijaya, 2014)
In the East Indonesia semiarid farming, the role of woman farmers covers work varying from management to labour. However, in the development program, gender internalization ignored woman farmers due to invisibility of women’s role. This occurs despite their significant contribution in the production and post harvest. Woman farmers are invisible before the policy makers, planners, and practitioners. As they are excluded from both the development program as well as that from the routine agricultural program, they do not benefit equally to the men when agricultural technology is introduced. Within the realm of gender main-streaming to promote the women farmers’ status as an equal. partner to the men a research methodology with feminist perspective to find out the women’s farmers vision about their agriculture food production. This paper discuss needs identification of agricultural technology by women farmers. The result is amazingly challenging for the agronomist to fulfill.Keywords: gender, appropriate technology with women’s perspective, traditional agriculture technology, women friendly technology development